Producción de pollos Broilers en tiempos de pandemia por COVID-19 en la zona centro norte de Manabí - Gilces Lectong, Julio Rafael (2022)
In order to establish the level of affectation that it presented in the productive activity of broilers in the north central zone of Manabí during the critical time of the COVID-19 pandemic (March to May 2020), a characterization of the production through the direct collection of data through the technique of applying surveys, carried out on government officials and producers in the area under study. From this information it was possible to verify the existence of five duly registered farms, which represented the study units identified as farm one, two, three, four and five. The research was of a non-experimental type, with a level of cross-sectional descriptive method, and showed that the production of chickens during the pandemic presented a decrease of 20% in farms one, two and three, farm four 42%, and farm five maintained its production. In all the farms evaluated there were limitations of the production process such as scarcity of raw material, increase in costs, increase in the value of medical supplies and decrease in the price of live chicken. It is concluded that there is a low number of farms registered by the regulatory body and a marked decrease in the production of broilers during the pandemic.